PELATIHAN MENGGUNAKAN SISTEM INFORMASI GEOGRAFIS LOKASI LEMBAGA SWADAYA MASYARAKAT DI KESBANGPOL PEKANBARU - Hardianto, Roki; Fajrizal, Fajrizal; Darmayunata, Yuvi (Jurnal Pengabdian Masyarakat Multidisiplin, 2020)
Community Service is carried out at the Office of National Unity and Politic (Kesbangpol) of Pekanbaru City, in the form of training of Pekanbaru Kesbangpol operators in managing Geographical Information System (GIS) on the mapping of registered and registered LSM. This dedication is a follow up to the research on the making of a Geographic Information System (GIS) on the mapping of LSM. It is hoped that by using this system, the data recording process of LSM registered at Kesbangpol will be more integrated and easily accessible to the public as mandated by the Law. This dedication is a form of real collaboration between the Faculty of Computer Science, University of Lancang Kuning with government agencies in this case the Kesbangpol Pekanbaru Office.